Aplicación de dos dosificaciones de micorrizas en diferentes momentos y su influencia en la morfología, fisiología y productividad del cacao Theobroma cacao L. en la parroquia Guadalupe, Zamora Chinchipe - Sisalima Ortega, Lady Yesenia (2022)
Cacao is one of Ecuador's main export products, being the “Nacional'' variety, the one that made Ecuador known in the world market, however, the low yield is due to poor management. Farmers carry out fertilization in an empirical way, which causes deficiency of nutrients and minerals essential for plants or reduces the assimilation of nutrients by the plant. The objective of this study was to test two doses of mycorrhizae (100% and 200%) at different times (one application, monthly applications and applications every three months) on Nacional cocoa plants, approximately 7 years old, in the productive stage, in the province of Zamora Chinchipe. A completely randomized design was established, with 7 treatments and 4 replications, T1= Control, T2= one application at 100%, T3= monthly applications at 100%, T4= one application at 100% every three months, T5= one application at 200%, T6= monthly applications at 200%, T7= one application at 200% every three months. Vegetative variables were evaluated: plant height, number of branches per plant, number of flowers per plant and productive variables such as fruit set percentage, ear length, ear diameter, number of ears per plant, ear index, ear weight, number of kernels per ear, kernel weight, fruit health, production and yield, to which an ANOVA was performed and correlated. No influence was found on vegetative variables, fruit set percentage, number of ears per plant, ear index, kernel weight, but there was an influence on ear length and diameter, ear weight, number of kernels per ear, production and yield. In conclusion, monthly applications of mycorrhizae at 100% obtained the highest values in all variables. These results contribute to improve cacao production in the Amazon region of Ecuador through the use of microorganisms that are environmentally friendly. Key words: mycorrhizae, vegetative variables, productive variables